Experimental Investigation of Phase Equilibria in the Bi-Cu-Ge System - Milosavljevic,Milan (2021)
Abstract Phase diagram of the Bi-Ce-Ge ternary system has been investigated experimentally and thermodynamically extrapolated by using Pandat software. Experimental results were obtained using differential thermal analysis (DTA), scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS), and X-ray powder diffraction (XRD) methods. Examined ternary samples belong to two isothermal sections at 400 and 600 °C as well as three vertical sections Bi-CuGe, Cu-BiGe, and Ge-BiCu. No ternary compound has been detected in the equilibrated samples from the selected isothermal sections. Based on the presented experimental data and available literature data, description of the ternary system has been developed. A reasonable agreement between the experimental data and the calculated phase equilibria was obtained. As an example, ternary Cu80Bi10Ge10 alloy was selected for solidification simulations according to Scheil and Lever Rule assumptions as well as for simulation of the total fraction of each solid at different temperatures, latent heat, and total heat.